ڕەوشى کۆمەڵایەتى دانیشتوانى کەمپى عەربەت توێژینەوەیەکى ئەنسرۆپۆلۆجیە - عبدالله, پ. د.ئاسۆ ئیبراهیم; حسن, بەختیار هادى (Sulaimani Journal for Humanities, 2023)
The issue of displacement and resettlement is one of the issues examined by sociology and anthropology. As the displaced leave their original land, they form part of the history of many local communities. Regardless of the causes of displacement, the cause of conflict can be military or internal conflict, or a result of natural disasters such as floods, earthquakes, etc. The research sheds light on the issue of internal displacement, especially the displaced from the village of Al-Bushhmeh in Salah Al-Din Governorate in 2014, after the arrival of ISIS and settled in the Arbat camp in the Sulaymaniyah governorate. This particular study describes the social situation of the residents of Arbat camp and describes the social structure of the research community through the social change between their families and members after more than seven years of displacement in Arbat camp. This research is considered the first anthropological research conducted in the Arbat camp for internally displaced persons. The research consists of three parts; the first part is the general guidelines of research. The second part has two sections; the first one talks about the societal foundation of Al-Bohshmuh inhabitants. And the second section talks about the relative-based system in its different forms. The third part has three sections. The first one talks about marriage and its different forms. The second section talks about family and the last one focuses on the conclusion of the research.